Naval Modernisation in Southeast Asia, Part Two Submarine Issues for Small and Medium Navies (Springer International Publishing, 2018)
This edited volume starts with an account of the submarine in naval warfare and moves on to review the nature and consequences of naval modernisation in Southeast Asia by considering their acquisition by the small and medium navies of the region. It explores the reasons for these navies taking on this very substantial and demanding challenge, the problems they are facing and the consequences of the deployment of submarines for regional stability. Given the backdrop of growing tensions over the South China Sea and increasing competition between the United States and China in the region, will the arrival of submarines in the area help or hinder the cause of peace? This volume will be of substantial interest not just to those interested in submarines and naval development but also to students and teachers concerned about the very volatile developing situation in and around the South China Sea. .